Rationale and Application of the Protocol S Anti–Vascular Endothelial Growth Factor Algorithm for Proliferative Diabetic Retinopathy - Sun, Jennifer K.; Glassman, Adam R.; Beaulieu, Wesley T.; Stockdale, Cynthia R.; Bressler, Neil M.; Flaxel, Christina; Gross, Jeffrey G.; Shami, Michel; Jampol, Lee M. (Ophthalmology (Rochester, Minn.), 2019)
To present the rationale, guidelines, and results of ranibizumab treatment for proliferative diabetic retinopathy (PDR) in Diabetic Retinopathy Clinical Research Network (DRCR.net) Protocol S. Post hoc analyses from a randomized clinical trial. Three hundred five participants (394 study eyes) having PDR without prior panretinal photocoagulation (PRP). Intravitreous ranibizumab (0.5 mg) versus PRP for PDR. Ranbizumab-assigned eyes (n = 191) received monthly injections for 6 months unless resolution was achieved after 4 injections. After 6 months, injections could be deferred if neovascularization was stable over 3 consecutive visits (sustained stability). If neovascularization worsened, monthly treatment resumed. Panretinal photocoagulation could be initiated for failure or futility criteria. Neovascularization status through 2 years. At 1 month, 19% (35 of 188) of ranibizumab-assigned eyes showed complete neovascularization resolution and an additional 60% (113) showed improvement. At 6 months, 52% (80 of 153) showed neovascularization resolution, 3% (4) were improved, 37% (56) were stable, and 8% (13) had worsened since the last visit. Among eyes with versus without resolved neovascularization at 6 months, the median (interquartile range) number of injections between 6 months and 2 years was 4 (1–7; n = 73) versus 7 (4–11; n = 67; P < 0.001). Injections were deferred in 68 of 73 eyes (93%) meeting sustained stability at least once during the study; 62% (42 of 68) resumed injections within 16 weeks after deferral. At 2 years, 43% (66 of 154) showed neovascularization resolution, 5% (7) showed improvement, 23% (36) were stable, and 27% (42) had worsened since the last visit. Only 3 eyes met criteria for failure or futility through 2 years. The DRCR.net treatment algorithm for PDR can provide excellent clinical outcomes through 2 years for patients initiating anti–vascular endothelial growth factor (VEGF) therapy for PDR. When choosing between anti-VEGF and PRP as first-line therapy for PDR, treatment decisions should be guided by consideration of the relative advantages of each therapeutic method and anticipated patient compliance with follow-up and treatment recommendations.